Psychosocial Management of the Patient With Duchenne Muscular Dystrophy - Colvin, Mary K; Poysky, James; Kinnett, Kathi; Damiani, Mario; Gibbons, Melissa; Hoskin, Janet; Moreland, Scott; Trout, Christina J; Weidner, Norbert (Pediatrics (Evanston), 2018)
In this article, we outline a comprehensive plan for the psychosocial management of patients with Duchenne muscular dystrophy (DMD) across the life span. In 2010, the Centers for Disease Control and Prevention sponsored the development of multidisciplinary management guidance for DMD, and in 2018, that guidance was updated. In the intervening years, a new emphasis was placed on studying and addressing the psychosocial issues that affect patients with DMD, driven in part by improved patient survival. Once viewed as ancillary to managing the significant medical needs of patients with DMD, it is now standard practice to integrate psychosocial management into the multidisciplinary management of the disease. It is also increasingly recognized that neurodevelopmental disorders in DMD occur at a higher rate than what was previously understood and that these disorders warrant early and intensive intervention. In this article, we expand on the content found in the 2018 DMD Care Considerations.